Resistência de genótipos de tomateiro ao ácaro rajado - Maruyama, Wilson Itamar [UNESP]; Toscano, Luciana Cláudia [UNESP]; Boiça Júnior, Arlindo L. [UNESP]; Barbosa, José Carlos [UNESP] (Associação Brasileira de Horticultura, 2002)
Avaliou-se a resistência de genótipos de tomateiro selvagens [Lycopersicon pennellii (LA 716), L. hirsutum var. glabratum (PI 126449, PI 134417), L. hirsutum (PI 127826, PI 127827), L. peruvianum (CGO 6707), L. peruvianum var. dentatum (WYR 2020, LA 111), L. peruvianum var. glandulosum (LA 1113-1, LA 1113-2)] e comerciais [(L. esculentum) Gem Pride, Santa Clara, e híbridos Bruna VFN, Carmem, Fortaleza, Débora Plus VFN] ao ácaro rajado (Tetranychus urticae). O número médio de ovos, fases imaturas (larvas, protoninfas e deutoninfas) e adultos por folíolo foi contado; o índice de preferência para oviposição (IPO) foi calculado. O delineamento experimental foi blocos ao acaso, com 6 repetições. Os genótipos LA 716, PI 126449, PI 134417, PI 127827, PI 127826 e Gem Pride apresentaram não-preferência para oviposição do ácaro rajado, sendo deterrentes quanto à classificação do IPO, enquanto os genótipos LA 111, WYR 2020, LA 1113-2 e LA1113-1 foram os mais preferidos para a oviposição e foram considerados como estimulantes pelo IPO.

The resistance of different tomato genotypes to spider mite (Tetranychus urticae) was evaluated. The wild genotypes evaluated were Lycopersicon pennellii (LA 716), L. hirsutum f. glabratum (PI 126449, PI 134417), L. hirsutum (PI 127826, PI 127827), L. peruvianum (CGO 6707), L. peruvianum f. dentatum (WYR 2020, LA 111), L. peruvianum f. glandulosum (LA 1113-1, LA 1113-2); and the commercial genotypes (L. esculentum) were Gem Pride, Santa Clara, and the F1 hybrids Bruna VFN, Carmem, Fortaleza and Débora Plus VFN. The number of eggs was counted, young phases (larvae, protonimphs, deutonimphs) and adults per leafleft. After the counting, the index of oviposition preference (IOP) also was calculated. The experiment was realized in randomized block design, with six replications. The LA 716, PI 126449, PI 134417, PI 127827, PI 127826 and Gem Pride genotypes showed non-preference for spider mite oviposition, being deterrents through IOP classification, while LA 111, WYR 2020, LA 1113-2 and LA1113-1 genotypes were the more preferred for oviposition and stimulants for oviposition by the IOP.
Resistance of tomato genotypes to spider mite
Keywords: Tetranychus urticae; Lycopersicon esculentum; L. pennellii; L. hirsutum; L. peruvianum; resistance of plant; Tetranychus urticae; Lycopersicon esculentum; L. pennellii; L. hirsutum; L. peruvianum; Resistência de plantas